COVID-19 mortality rate and its determinants in Ethiopia: a systematic review and meta-analysis - Wondmeneh, Temesgen Gebeyehu; Mohammed, Jemal Abdu (Frontiers in Medicine, 2024)
Background The COVID-19 mortality rate continues to be high in low-income countries like Ethiopia as the new variant’s transmission expands and the countries’ limited capacity to combat the disease causes severe outcomes, including deaths. The aim of this study is to determine the magnitude of the COVID-19 mortality rate and its determinants in Ethiopia. Methods The main electronic databases searched were PubMed, CINAHL, Google Scholar, and African journals online. The included studies’ qualities were assessed independently using the Newcastle-Ottawa scale. The data was extracted in Microsoft Excel spreadsheet format. The pooled effect size and odds ratios with 95% confidence intervals across studies were determined using the random-effects model. I2 is used to estimate the percentage of overall variation across studies due to heterogeneity. Egger’s test and funnel plot were used to find the published bias. A subgroup analysis was conducted. The effect of a single study on the overall estimation was determined by sensitivity analysis. Results A total of 21 studies with 42,307 study participants were included in the final analysis. The pooled prevalence of COVID-19 mortality was 14.44% (95% CI: 10.35–19.08%), with high significant heterogeneity (I2 = 98.92%, p < 0.001). The risk of mortality from COVID-19 disease was higher for patients with comorbidity (AHR = 1.84, 95% CI: 1.13–2.54) and cardiovascular disease (AHR = 2, 95% CI: 1.09–2.99) than their counterparts without these conditions. Conclusion A significant number of COVID-19 patients died in Ethiopia. COVID-19 patients with comorbidities, particularly those with cardiovascular disease, should receive special attention to reduce COVID-19 mortality. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, registration identifier (ID) CRD42020165740.